Effects of magnesium ferrite biochar on the cadmium passivation in acidic soil and bioavailability for packoi (Brassica chinensis L.). (1st December 2019) - Gao, Xing; Peng, Yutao; Zhou, Yaoyu; Adeel, Muhammad; Chen, Qing
Abstract: Biochar (BC) and magnesium ferrite (MF) have been used in effective adsorption of cadmium (Cd) in aqueous environment, whereas little is known about the effect of their composite on Cd adsorption and Cd-contaminated soil remediation. In this study, biochar (BC), magnesium ferrite (MF) and biochar assembled with magnesium ferrite (MB) were prepared for Cd adsorption and then applied in soils (1–2% w/w ) to investigate their effects on Cd passivation by performing leaching experiments and early stage seeding growth test for packoi ( Brassica chinensis L . ). Compared with the BC and MF, the MB showed greater adsorption property for Cd at aqueous solution (31.3 mg/g) and amended soils (1.85 mg/g at 2% applied rate) based on the isotherms studies. Besides, the MB performed the better passivation ability in reduction of the bioavailable Cd and seeding growth experiment. Solid state analysis of the materials before and after leaching indicated that the passivation mechanism may be dominated by ion exchange and surface complexation. Principal component analysis revealed that the soil pH and adsorption capacity had the strong correlation with the contents of bioavailable-Cd and seedling growth. These results indicated that MB could be used as an efficient amendment in Cd contaminated soil for reducing bioavailable Cd concentrations and improving plant growth. Graphical abstract: Image 1 Highlights: MB, BC and MF were fabricated and applied in soil for Cd remediation. MB was most effective in reducing soil bioavailable Cd. Well dispersion and extra adsorption sites in MB facilitated Cd binding. MB effectively mitigated the cadmium toxicity on packoi seedling growth.